A study of multicomponent gas mixtures using various analytical methods for stack emission measurements - Marebane, Prelly Mohweledi (My University, 2017)
Multicomponent gas mixtures are inherently challenging to produce in the laboratory because of matrix effects, boiling points and reactivity amongst other factors. Therefore, methods must be continuously developed to control these challenges. The purpose of this work was to study these complex gas mixtures to improve their measurements with emphasis on the reduction of uncertainty. There are three critical steps to be followed in gas metrology for primary reference gas mixtures of the highest metrological level; purity analysis of source gases, gravimetric preparation and verification/validation which includes stability testing. Purity analysis of select source gases was quantified using various techniques. This methodology incorporated the use of molar masses and their uncertainties in order to obtain purity values for the chemical composition of gas mixtures. While many preparation methods such as permeation and dynamic methods are available, a static gravimetric method was used to prepare the complex stack and automotive gas mixtures following International Standard Organisation: 6142-1. For the mole fraction range of interest, four components (carbon dioxide, carbon monoxide, sulphur dioxide and nitric oxide) excluding propane, were obtained from analysis by non-dispersive spectroscopy techniques calibrated by several standard gas mixtures of different mole fractions. Propane was analysed by a gas chromatograph coupled with flame ionisation detection. Multipoint calibration was used to evaluate the linearity or nonlinearity of the detector. The final results for the stack gas mixture components showed an achievement of 0.4% to 0.8% percentage relative expanded uncertainty and 0.4% to 1.3% for carbon dioxide depending on the matrix of the standard gas mixtures used, 0.5% to 1% for propane, 0.8% to 1.8% for nitric oxide, 2% to 6% for carbon monoxide and 0.3% to 2.3% for sulphur dioxide. One of the most important suppositions drawn was the incidence of synergistic effects associated with calibration by nonrepresentative standard gas mixtures when these were used for analysis for some of the components of stack mixtures. To evaluate improvements in measurement capability, the results of the current work were compared to the data of the laboratory in 2008-2011 and there was an improvement in the measurement of carbon dioxide, carbon monoxide, propane and nitric oxide. These improvements are attributed to rigorous purity analysis of starting materials, reduction of uncertainty and developments in measurement expertise. In this work, different measurement and calibration methods were used to analyse the components of the new stack gas mixtures. The stability of these components was evaluated by analysing them at different times and the statistical D-test was used to check for significant instability. An unknown stack sample was compared with the standard gas mixtures prepared for this work. In combination with same matrix and same concentrations, single point calibration was found suitable for stack gas measurement. To reiterate the concept of matrix effect, the results of carbon dioxide in a mixture containing carbon monoxide and oxygen as well in nitrogen, were used to show how differences in matrix often give erroneous results and same conclusions cannot be made for different mixtures. While the data of this measurement was unsatisfactory, an improved method developed for this type of emission multicomponent was very successful. Emission industries also require automotive primary reference gas mixtures. These are equally important and complex multicomponent mixtures measured and improved in this work. A very precise and repeatable single point method was developed for the analysis of the components of automotive mixtures. The repeatability of the gas chromatography method was 0.2% for oxygen, 0.1% for carbon monoxide, 0.5% for carbon dioxide and 0.3% for propane. The percentage relative expanded uncertainty was 0.4% for oxygen, 0.8% for carbon monoxide, 0.8% for carbon dioxide and 0.5% for propane. However, its limitation was the use of different calibration gases for each analysis. This led to inconsistencies in the calculated mole fractions, non-predictability and instability. A proficiency testing scheme was coordinated by the laboratory for automotive emission as part of this study. Given the complexity of the samples, the work aimed to check any improvements that could be made to the capability of measurement over the years. This new method using gas chromatography coupled with different detectors (residual gas analyser) was successful in verifying the gravimetric values very V accurately. Finally, the results of the stack gas mixtures were ≤1% relative except carbon monoxide and ≤1% for automotive mixtures. This work aimed to support the emission industry by providing it with representative and accurate reference gas mixtures, extend the accreditation scope of the laboratory and improve its calibration and measurement capability for multicomponent gas mixtures.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfillment of the requirements for the degree Master of Science. Johannesburg, 2017.
Keywords: Gas manufacture and works; Metrology